Transforming Children's Education with Technology: The Role of AI, IoT, and Gamification in Learning - Nurhakim, Lukman (LP2M IAI Al-Khairat Pamekasan, 2025)
This study explores the transformative impact of technology on children's education, specifically examining the roles of Artificial Intelligence (AI), the Internet of Things (IoT), and gamification in the learning process. The research employs a qualitative approach with case studies conducted in primary and secondary schools that have integrated these technologies into their educational practices. Data were collected through interviews with teachers, school principals, and parents, as well as classroom observations and document analysis. The findings reveal that AI offers personalized learning experiences by tailoring content to individual students' needs, while IoT enhances classroom interactivity and engagement through real-time monitoring and smart devices. Furthermore, gamification has proven effective in boosting student motivation and participation by incorporating game-like elements such as rewards and challenges into the learning environment. Despite the positive impacts, challenges such as the digital divide, infrastructure limitations, and the need for teacher training remain obstacles to widespread implementation. This study concludes that while technology offers significant potential for educational transformation, it requires a balanced approach that includes adequate support for educators and infrastructure development, ensuring that all students can benefit equally from technological advancements.